MEMBANGUN APOLOGETIKA MISI DI ERA AKADEMIK SEKULAR - Elia Boen Eni (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2026)
The secular academic era presents significant challenges to the existence of Christian faith, particularly within the context of higher education that increasingly places rationalism and relativism as the primary foundations of thought. This condition calls for a missional apologetics that is not only capable of defending faith argumentatively, but also demonstrates spiritual integrity and prophetic courage amid intellectual pressures. This study aims to examine the relevance of 1 Kings 17:1–6 as a theological foundation for constructing missional apologetics in the secular academic era. The research employs a qualitative method through a library research approach and biblical analysis. The findings reveal that the figure of Elijah in 1 Kings 17:1–6 embodies three principal dimensions of missional apologetics: the courage to proclaim God’s truth within a culture that rejects Him, total dependence upon God’s providence, and spiritual consistency in fulfilling the missional calling. In the context of modern academia, these principles serve as an essential foundation for believers to present an intellectual, relevant, and transformative witness of faith. Therefore, missional apologetics should not merely be understood as a theoretical defense of faith, but also as an expression of prophetic spirituality capable of responding to the challenges of secularization within the academic world.